2021
DOI: 10.3390/recycling6010003
|View full text |Cite
|
Sign up to set email alerts
|

Prospects of Red King Crab Hepatopancreas Processing: Fundamental and Applied Biochemistry

Abstract: Since the early 1980s, a large number of studies on enzymes from the red king crab hepatopancreas were conducted. They have been relevant both from a fundamental point of view in terms of studying the enzymes of marine organisms and in terms of rational natural resource management aimed to obtain new valuable products from the processing of crab fishing waste. Most of these works were performed by Russian scientists due to the area and amount of waste of red king crab processing in Russia (or the Soviet Union)… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 36 publications
0
7
0
Order By: Relevance
“…The rate of HA cleavage is an order of magnitude higher than the rate of hydrolysis by a commercial analog (Lydazum) when normalized to the total protein in the studied preparations of hyaluronidase. Since red king crab catch amounts to large volumes in different countries generating hepatopancreas as a waste product of crab processing it is safe to assume that it generates enough of a raw material for production of a new potential medical drug hyaluronidase on industrial scale 20 .…”
Section: Introductionmentioning
confidence: 99%
“…The rate of HA cleavage is an order of magnitude higher than the rate of hydrolysis by a commercial analog (Lydazum) when normalized to the total protein in the studied preparations of hyaluronidase. Since red king crab catch amounts to large volumes in different countries generating hepatopancreas as a waste product of crab processing it is safe to assume that it generates enough of a raw material for production of a new potential medical drug hyaluronidase on industrial scale 20 .…”
Section: Introductionmentioning
confidence: 99%
“…Our research has revealed that the muscles are a structural tissue characterized by a high protein content (19.41%) and low fat content (0.87%), which aligns with previous findings reported for this species by Chen et al [ 17 ] and Wang et al [ 19 ]. The hepatopancreas, a multifunctional organ responsible for lipid and cholesterol absorption and storage [ 35 , 36 ], exhibits a high lipid content ranging from 15.01% to 45.09% in Chinese mitten crabs [ 19 , 24 ], while the protein content is relatively low, ranging from 6.29% to 10.28% [ 19 , 31 ]. In the examined crabs from the Odra River estuary, the fat content in the hepatopancreas was lower (11.67%), while the protein content was higher (13.62%).…”
Section: Discussionmentioning
confidence: 99%
“…It is considered a delicacy that is valued by food markets and has a stable demand supporting high prices. Moreover, by-products of P. camtschaticus such as hepatopancreas, hemolymph, and shells are also considered important sources for chitin, chitosan, proteolytic enzymes, fatty acids, and other substances [16][17][18].…”
Section: Introductionmentioning
confidence: 99%